Role of the Fractalkine Receptor in CNS Autoimmune Inflammation: New Approach Utilizing a Mouse Model Expressing the Human CX3CR1I249/M280 Variant - Cardona, Sandra M.; Kim, Sangwon V.; Church, Kaira A.; Torres, Vanessa O.; Cleary, Ian A.; Mendiola, Andrew S.; Saville, Stephen P.; Watowich, Stephanie S.; Parker-Thornburg, Jan; Soto-Ospina, Alejandro; Araque, Pedronel; Ransohoff, Richard M.; et al. (Frontiers in Cellular Neuroscience, 2018)
Multiple sclerosis (MS), an inflammatory demyelinating disease of the central nervous system (CNS) is the leading cause of nontraumatic neurological disability in young adults. Immune mediated destruction of myelin and oligodendrocytes is considered the primary pathology of MS, but progressive axonal loss is the major cause of neurological disability. In an effort to understand microglia function during CNS inflammation, our laboratory focuses in the fractalkine/CX3CR1 signaling as a regulator of microglia neurotoxicity in various models of neurodegeneration. Fractalkine (FKN) is a transmembrane chemokine expressed in the CNS by neurons and signals through its unique receptor CX3CR1 present in microglia. During experimental autoimmune encephalomyelitis (EAE), CX3CR1 deficiency confers exacerbated disease defined by severe inflammation and neuronal loss. The CX3CR1 human polymorphism I249/M280 present in ~20% of the population exhibits reduced adhesion for FKN conferring defective signaling whose role in microglia function and influence on neurons during MS remains unsolved. The aim of this study is to assess the effect of weaker signaling through hCX3CR1I249/M280 during EAE. We hypothesize that dysregulated microglial responses due to impaired CX3CR1 signaling enhance neuronal/axonal damage. We generated an animal model replacing the mouse CX3CR1 locus for the hCX3CR1I249/M280 variant. Upon EAE induction, these mice exhibited exacerbated EAE correlating with severe inflammation and neuronal loss. We also observed that mice with aberrant CX3CR1 signaling are unable to produce FKN and Ciliary Neurotrophic Factor (CNTF) during EAE in comparison to WT. Our results provide validation of defective function of the hCX3CR1I249/M280 variant and the foundation to broaden the understanding of microglia dysfunction during neuroinflammation.